Wardah's Digital Marketing Strategy through Islamic Branding, Influencer Marketing, and Flash Sale Programs to Increase Online Shopping Decisions on the Shopee Platform - Chalid Imran Musa; Azlan Azhari; Kristina Parinsi (Economics and Business Journal (ECBIS), 2026)
The rapid growth of digital technology and e-commerce has transformed consumer behavior, particularly in online beauty product purchases. This study aims to examine the influence of Islamic Branding, Influencer Marketing, and Flash Sale on online shopping decisions for Wardah beauty products on Shopee. Using a quantitative approach, data were collected from 100 respondents in Makassar who had purchased Wardah products online. The data were analyzed using multiple linear regression with SPSS 26. The results indicate that Islamic Branding, Influencer Marketing, and Flash Sale each have a positive and significant effect on online shopping decisions. Simultaneously, these three variables contribute 51% to consumer purchasing decisions, showing that a combination of religiosity-based branding, social influence, and urgency-driven promotion effectively encourages consumer purchases. The findings suggest that integrating Islamic values with digital marketing strategies enhances consumer trust and purchase intention in the halal beauty market.